Efeitos de sentido em dissertações escolares: A discursivização da mulher - Almeida, Ana Paula Fagundes Guimarães de (2018)
The feminine universe is quite portrayed in various environments of society such as advertising, humorous TV programmes, billboards, written texts, images, songs, that is to say, in several textual genres. In this aspect, it is built an image of the woman that, for most part of the time, is unnoticed by society’s eye and, if it is formed, mostly by young people and teenagers, many of them won’t worry about making a more critical analysis. Therefore, if we don’t attribute to ourselves a certain criticality, we may not analyze many critical and political aspects concerning the woman. Before this, this work aims to reflect about the discourse, in its ideological nature, concerning the sayings resumed about the woman’s thematic, trough the analyzes of the corpus of this work, which was constituted by school dissertations produced by students from the 9° year of Elementary school, from a public school in the municipality of Santanópolis. The present research was based in the assumptions of the Pêcheux’s discourse analysis. We have analyzed the school dissertations with the objective of assess the effects of sense produced by the students trough the conditions of production and its ideological formations (FI) and discursive formations (FD). For this purpose, it was realized a reading workshop aiming the students to produce school texts from the reading of various textual genres that approached the woman’s thematic. Thus, it was offered diverse texts such as: reporting, song lyrics, advertising, tale, cartoon and comic strips. The discourses were analyzed in the attempt of noticing to what ideological formations and discursive formations these students are affiliated, as well as the attempt of noticing what production conditions and ideology they are summoned, as well as we sought understand from the discourse analyzes’ mechanisms the positioning of the students and of the society towards the woman. Accordingly with the presented analyzes and surveyed data it is possible to notice that the discourses are mobilized from the already said in another spaces and of a discursive memory already established in the society, however there are some ruptures coming from some students when they do not identify themselves with the dominant ideology. We could also notice that some discourses are wrapped in the meaning silence.